2023
DOI: 10.46234/ccdcw2023.218
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Varicella Outbreaks — China, 2006–2022

Miaomiao Wang,
Xudong Li,
Meiying You
et al.

Abstract: Introduction Varicella outbreaks significantly disrupt schools and other child-centered institutions. This study aimed to identify patterns and epidemiological features of varicella outbreaks in China from 2006 to 2022. Methods Data were extracted from outbreak reports submitted to the Public Health Emergency Reporting Management Information System within the specified timeframe. Analytical methods included Spearman correlation tests and the Mann-Kendall trend tests, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Standardized diagnostic procedures have played a crucial role in achieving this (8)(9). Additionally, certain regions have heightened their management of varicella cases to ensure accurate reporting and a more representative incidence level (2,4). Furthermore, the impact of global warming on the risk of varicella cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized diagnostic procedures have played a crucial role in achieving this (8)(9). Additionally, certain regions have heightened their management of varicella cases to ensure accurate reporting and a more representative incidence level (2,4). Furthermore, the impact of global warming on the risk of varicella cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of varicella is primarily observed in children, although recent studies have shown an increasing incidence rate and proportion among the elderly population (1)(2). Previous research has mostly focused on describing the epidemiological characteristics of varicella in specific provincial-level administrative division (PLAD) or cities in China (3)(4). However, there is a lack of studies investigating long-term patterns of varicella incidence by gender, age, period, and cohort.…”
mentioning
confidence: 99%